Classification of the treble clef zinc finger: noteworthy lessons for structure and function evolution - Kaur, Gurmeet (Sci Rep, 2016)
Treble clef (TC) zinc fingers constitute a large fold-group of structural zinc-binding protein domains that mediate numerous cellular functions. We have analysed the sequence, structure, and function relationships among all TCs in the Protein Data Bank. This led to the identification of novel TCs, such as lsr2, YggX and TFIIIC τ 60 kDa subunit, and prediction of a nuclease-like function for the DUF1364 family. The structural malleability of TCs is evident from the many examples with variations to the core structural elements of the fold. We observe domains wherein the structural core of the TC fold is circularly permuted, and also some examples where the overall fold resembles both the TC motif and another unrelated fold. All extant TC families do not share a monophyletic origin, as several TC proteins are known to have been present in the last universal common ancestor and the last eukaryotic common ancestor. We identify several TCs where the zinc-chelating site and residues are not merely responsible for structure stabilization but also perform other functions, such as being redox active in C1B domain of protein kinase C, a nucleophilic acceptor in Ada and catalytic in organomercurial lyase, MerB.